2022
DOI: 10.3389/fimmu.2022.980508
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a lactic acid metabolism-related gene signature contributes to predicting prognosis, immunotherapy efficacy, and tumor microenvironment of lung adenocarcinoma

Abstract: Lactic acid, once considered as an endpoint or a waste metabolite of glycolysis, has emerged as a major regulator of cancer development, maintenance, and progression. However, studies about lactic acid metabolism-related genes (LRGs) in lung adenocarcinoma (LUAD) remain unclear. Two distinct molecular subtypes were identified on basis of 24 LRGs and found the significant enrichment of subtype A in metabolism-related pathways and had better overall survival (OS). Subsequently, a prognostic signature based on 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…We also constructed a nomogram to improve the predictive value of the formula for evaluating the prognosis of patients with HCC. In summary, our study clari ed the signi cance of exosome-related genes in the development of NAFLD-related HCC.Recently, there are many models constructed with diseases-related genes for the diagnosis and prognosis of various diseases including HCC [13,14]. It has been revealed that the diagnostic e ciency of multigene model is usually higher than that of single-gene model [15].…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…We also constructed a nomogram to improve the predictive value of the formula for evaluating the prognosis of patients with HCC. In summary, our study clari ed the signi cance of exosome-related genes in the development of NAFLD-related HCC.Recently, there are many models constructed with diseases-related genes for the diagnosis and prognosis of various diseases including HCC [13,14]. It has been revealed that the diagnostic e ciency of multigene model is usually higher than that of single-gene model [15].…”
mentioning
confidence: 68%
“…Liang et al constructed a formula with 10 ferroptosis-related genes to predict overall survival (OS) time of HCC patients [13]. Zhao et al identi ed a formula with 5 lactic acid metabolism-related genes to predict prognosis and immunotherapy e cacy of lung adenocarcinoma [14]. Chen et al developed a ve-gene prognostic model to predict the risk and prognosis of colon cancer [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The nomogram is frequently used to determine the prognosis of cancer [ 39 ]. Some nomograms regarding the precise prediction of LUAD patients’ prognoses have been demonstrated in previous studies [ 40 , 41 ]. After combining the risk signature with other clinical characteristics, precise nomograms for OS, PFS, and DFS that are clinically applicable were developed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan-Meier (KM) survival analysis was used to test the survival difference between the two subgroups. In addition, we utilized ROC curves to compare the effectiveness of our model with previous studies ( 16 19 ).…”
Section: Methodsmentioning
confidence: 99%